Examining export trade and corporate innovation: A multiphase difference-in-differences method - Donghua Zhou; Jianfei Peng; Xue Gao (China Journal of Accounting Research, 2021)
Using a multiphase difference-in-differences model, this study investigates the relationship between export trade and the corporate technological innovation of listed companies. It reveals that engaging in export trade increases corporate innovation input and output. In terms of patent output, export trade greatly promotes the output of invention patents and utility model patents with a high technological content. These conclusions remain valid after a series of robustness and endogeneity tests. Regarding the mechanisms of the observed relationships, export trade stimulates corporate technological innovation mainly by realizing economies of scale and increasing risk-taking. The positive correlation between export trade and corporate technological innovation is strongest among state-owned enterprises, non-high-tech enterprises, enterprises based in central and eastern China, enterprises engaged in general trade, and enterprises exporting to developed economies. Given the growing trade frictions ongoing at the time of writing, the conclusions of this study provide vital practical guidance and empirical evidence for a national strategy of innovation-driven development.
Keywords: 650; Economies of scale; Export trade; Risk-taking; Technological innovation